Traumatic verses : on poetry in German from the concentration camps, 1933-1945 - Nader, Andrés José 1968- (Studies in German literature, linguistics and culture, 2007)
Literary activities in the camps -- Identity under threat -- "Everyday life" in the concentrationary universe -- Communicating torture -- Contemporaneous poetry in the Third Reich